State Bar Pro Bono Awards Reception-Costa Mesa - Watkins, Howard::::::::: (1983)
Hal Bolen holding his State Bar President's Pro Bono Award, Tomar Mason, Fresno County Bar Association President Doug Jensen holding Pro Bono Award